Pengaruh Karakteristik Perusahaan dan Kepemilikan terhadap Utang Perusahaan Real Estat yang Terdaftar di Bursa Efek Indonesia Periode 2008 - 2013 - Gunawan Gunawan (Jurnal Keuangan dan Perbankan, 2016)
This research was aimed to elaborate the influences of corporate and ownership characteristics (as independent variabels) to its debt decision (as dependent variabel). Corporate characteristic was measured by its tangible assets, growth opportunity and RoI as profitability, whilst ownership characteristic was measured by its managerial ownership. Debt decision was measured by debt ratio between interest bearing notes to total assets. 32 listed real estat companies in Indonesia Stock Exchange were as its research’ sampling, especially which categorized in sub-sector property and real estat. Eviews 8 was used as statistical tools to exercise the secondary data. Results of the research were tangible assets has significant (positive) impact while profitability has (negative) impact to debt decision. It was consistent with the hypothesis of the research which stated (real estat) corporate characteristic has a dominant proportion of tangible assets in term of real estat inventory, developed area, investment property and fixed assets. All of these kind of tangible assets have a capability in delivering significant profit. The research also proved that variabel of growth has (negative) not significant impact. Managerial ownership as ownership characteristic, has (significant) impact to debt decision.